SUMMARISING AS A PEDAGOGICAL STRATEGY FOR ENHANCING GRAMMAR ACCURACY AND WRITING QUALITY AMONG GRADE 12 EFAL LEARNERS - Motlhaka Hlaviso (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
English writing is increasingly important in both educational and professional contexts in non-native English-speaking countries. Several studies have used summary writing strategies to enhance learners’ reading comprehension. However, few studies have examined the relationship between summarising and improvements in grammar accuracy, organisation, and overall writing quality. Therefore, this study investigates whether summarising as an instructional strategy enhances the grammar accuracy and writing quality of English First Additional Language (EFAL) learners. The study adopted a convergent mixed-method research design in which quantitative and qualitative data were collected concurrently, analysed separately, and merged during interpretation. Simple random sampling was used to select 50 Grade 12 EFAL learners and purposive sampling was used to select two EFAL teachers. A pre-test on summary writing was administered prior to the six-week summarising intervention. The post-test mean scores were consistently higher than the pre-test mean scores, indicating improvement in learners’ writing abilities after the intervention. The findings suggest that summarising effectively enhances learners’ vocabulary, grammar accuracy, and overall writing quality. The study has implications for learners, curriculum development and future research. For Grade 12 EFAL learners, summarising helps them to become independent writers by enabling them to organise ideas, reduce repetition, and communicate information effectively, which may also improve examination performance. For curriculum development, curriculum planners and teachers may incorporate structured summarising activities, comprehension-based writing tasks, and grammar-focused exercises. Future studies may also investigate the effectiveness of summarising across different educational contexts, grade levels, and language proficiency groups.